Histochemické vlastnosti hlenu v epiteliálních nádorech tlustého streva - Jirková, A (Ceskoslovenska patologie, 1981)
In a group of 9 polypous adenomas of the rectum and 27 adenocarcinomas of the large intestine histochemical properties of mucus were investigated. Malignization in the large intestine was associated with the disappearance of O-acyl esters of sialic acids, the presence of which was detected by the method PB KOH PAS only focally, mainly in an extracellular localization in 21.7% of all cases. In tubular adenocarcinomas (16 cases) mixed mucus with a different content of PAS+ mucosubstances predominated. With the PAS AM 2.5 method bluish violet to magenta colouration. Sulphomucin was not proved in these tumours, O-acyl esters of sialomucin only twice. Mucus with more acid histochemical properties (PAS AM 2.5 blue colouration) with sulphomucin (alcioanophilia at pH 1) was secreted by carcinomas of papillary structure (7 cases), the majority intensely mucus forming similarly as villous adenoma. We may therefore, consistent with data in the literature, assume their histogenetic relationship.
Keywords: Mucins; adenokarcinom; tlusté střevo; Humans; Sialomucins; histocytochemie; hlen; Mucus; Intestinal Neoplasms; Intestine, Large; sialomuciny; Adenocarcinoma; střevní nádory; lidé; muciny; Histocytochemistry